Immune humoral response of young lambs naturally infested by oestrus ovis (Diptera: Oestridae) - Da Silva, Bruna Fernanda; Bassetto, César Cristiano [UNESP]; Do Amarante, Alessandro Francisco Talamini [UNESP] (FapUNIFESP (SciELO), 2018)
Twenty-six newborn lambs were evaluated for 21 weeks, from birth to slaughter, to assess their plasma anti-Oestrus ovis immunoglobulin (IgG) using the ELISA technique. On the last day of sampling, all the lambs were slaughtered and O. ovis larvae were recovered, quantified and identified according to the larval stage. High levels of IgG were observed over the first three weeks of life, thus indicating that antibodies are transferred via colostrum from ewes to lambs. Afterwards, the antibody levels declined progressively until the lambs were 11 weeks of age and subsequently started to increase again when they were around 13 weeks of age, reaching the apex on the last week of sampling. All the lambs were parasitized with different larval stages of O. ovis, with an average of 39 larvae per lamb, and the intensity of the infestation ranged from 10 to 97 larvae. However, there was non-significant correlation coefficients between IgG levels and O. ovis larval burden (P > 0.05). In conclusion, although the lambs became infested with O. ovis at an early age, the larval burden was not associated with specific IgG levels.
Resposta imune humoral de cordeiros jovens naturalmente infestados por oestrus ovis (Diptera: oestridae)
Keywords: Dyspnea; Immune response; Immunoglobulin G; Myiasis; Sheep